2014
DOI: 10.3386/w20632
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Time-Consistent Government Debt Maturity

Abstract: This paper develops a model of optimal government debt maturity in which the government cannot issue state-contingent bonds and cannot commit to fiscal policy. If the government can perfectly commit, it fully insulates the economy against government spending shocks by purchasing short-term assets and issuing long-term debt. These positions are quantitatively very large relative to GDP and do not need to be actively managed by the government. Our main result is that these conclusions are not robust to the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…Other papers explore the optimal maturity structure of entire debt portfolios and their implications on optimal taxation and insurance against fiscal shocks, among others, Barro (1979), Lucas and Stokey (1983), Angeletos (2002), Buera and Nicolini (2004), and Debortoli et al (2017).…”
mentioning
confidence: 99%
“…Other papers explore the optimal maturity structure of entire debt portfolios and their implications on optimal taxation and insurance against fiscal shocks, among others, Barro (1979), Lucas and Stokey (1983), Angeletos (2002), Buera and Nicolini (2004), and Debortoli et al (2017).…”
mentioning
confidence: 99%
“…In economies without capital, we show that the government debt maturity is a key variable: longer debt calls for a longer commitment horizon. Consistent with this finding, Debortoli et al (2016) show that the welfare cost of lack of commitment is large and 5 A partial exception is Klein and Ríos-Rull (2003): in their setup, the government can set capital taxes one period ahead, but only current labor taxes. They show that capital taxes are on average high, compared to the FC equilibrium which has average capital taxes near zero.…”
Section: Introductionmentioning
confidence: 68%
“…Buera and Nicolini (2004) and Angeletos (2002) represent benchmark specifications in an incomplete market setting with debt of different maturities. These models fail to observe typical treasury behavior that more recent literature tries to replicate by means of restricting the government from going short in any maturity (Lustig, Sleet, and Yeltekin (2008), restricting the government's ability to commit (Debortoli et al, 2017), tying model closer to observed asset prices (Bhandari et al, 2017), considering the price impact of each issuance of an impatient government (Bigio, Nuño, & Passadore, 2018) and restricting the government ability to rebalance its portfolio (Faraglia et al, 2018).…”
Section: Literaturementioning
confidence: 99%